2008
DOI: 10.3354/ab00081
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on the recruitment process inferred from otolith stable isotopes in Merluccius merluccius off the Balearic Islands

Abstract: Oxygen (δ 18 O) and carbon (δ 13 C) isotope ratios in sagittal otoliths were analysed in recruits and juveniles of European hake Merluccius merluccius L. caught in the northwest (Sóller, SO) and south (Cabrera, CA) of the Island of Mallorca (western Mediterranean) over 2 consecutive years (2003 and 2004). The analytical method used allowed data to be gathered on both environmental and trophic conditions experienced by fish during the pelagic early life stages (registered in the composition of the inner part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…They noted differing tendencies in the predictive error of the two equations, which indicated the species-specific fractionation relationship for Patagonian toothfish had a distinctively different slope. Hidalgo et al (2008), however, used the cod-specific fractionation equation estimated by Høie et al (2004) on European hake (Merluccius merluccius (L.)), also a Gadiform, and reproduced temperatures within the range expected from temperature measurements of the water. Høie et al (2004) suggested physiological adaptations to specific environmental conditions might influence the otolith isotopic composition and result in differences in oxygen fractionation.…”
Section: Discussionmentioning
confidence: 99%
“…They noted differing tendencies in the predictive error of the two equations, which indicated the species-specific fractionation relationship for Patagonian toothfish had a distinctively different slope. Hidalgo et al (2008), however, used the cod-specific fractionation equation estimated by Høie et al (2004) on European hake (Merluccius merluccius (L.)), also a Gadiform, and reproduced temperatures within the range expected from temperature measurements of the water. Høie et al (2004) suggested physiological adaptations to specific environmental conditions might influence the otolith isotopic composition and result in differences in oxygen fractionation.…”
Section: Discussionmentioning
confidence: 99%
“…The relative contribution of these various factors to otolith carbon isotope ratios is likely to vary both in space and in time, and among species. Both isotope ratios have been used successfully as natural tags for fish stock discrimination studies (Edmonds and Fletcher, 1997;Bastow et al, 2002;Gao et al, 2004;Huxham et al, 2007;Dufour et al, 2008;Hidalgo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The initial rapid enrichment in juvenile and young adult fish is believed to result from an increase in the trophic level of the fish with age, probably concomitant with a shift in diet to higher trophic levels (e.g. Schwarcz et al 1998;Begg & Weidman 2001;Hidalgo et al 2008). Subsequently, metabolic rate (and metabolic contribution) would be expected to decrease with age (Schwarcz et al 1998).…”
Section: Figurementioning
confidence: 99%